RMPS: religious & philosophical questions - Walker, Joe; Jenkins, Kate (Dynamic learning, 2018)
This second edition ensures that the content of this leading textbook is fully up to date with arrangements for the Religious and Philosophical Questions section of the National 5 RMPS course. - Designed to help learners to develop the required knowledge and skills - Provides examples of assessment tasks to support learners as they prepare to tackle the final exam - Includes a range of stimulating prompts and classroom activities